2017
DOI: 10.1073/pnas.1619003114
|View full text |Cite
|
Sign up to set email alerts
|

Computer vision uncovers predictors of physical urban change

Abstract: Which neighborhoods experience physical improvements? In this paper, we introduce a computer vision method to measure changes in the physical appearances of neighborhoods from time-series street-level imagery. We connect changes in the physical appearance of five US cities with economic and demographic data and find three factors that predict neighborhood improvement. First, neighborhoods that are densely populated by college-educated adults are more likely to experience physical improvements-an observation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
143
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(147 citation statements)
references
References 36 publications
(25 reference statements)
2
143
0
2
Order By: Relevance
“…The GVI offers a link between visual perception and socio-economic data at the block level, and Li's studies have proven this notion [36,37]. In addition, using computer vision algorithms can aid in quantitative batch processing, offering clear efficiency improvements and reducing labour [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The GVI offers a link between visual perception and socio-economic data at the block level, and Li's studies have proven this notion [36,37]. In addition, using computer vision algorithms can aid in quantitative batch processing, offering clear efficiency improvements and reducing labour [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of creative industries in the egohood also seems to have an impact on price, confirming the preliminary results of Hristova et al [14] in London and New York. It is worth noting that, despite the use of many urban co-variates, visual appearance is one of the most important predictive factors for housing value, as similarly proven for other outcomes such as crime [25], happiness [24] and presence of people [13].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, they found that, safety perception being equal, these crimes were more related to areas that looked more upper class. Other researchers used a computer vision algorithm, that analysed time-series street-view imagery of five US cities, to study the relationship between physical changes of city neighbourhoods and demographic data (i.e., population density and share of residents with college education) [29]. Results from this study suggested that: (i) neighbourhoods more densely populated by adults with college education were more likely to undergo processes of urban change; (ii) neighbourhoods that had better initial appearances tended to undergo larger positive improvements; and (iii) positive neighbourhood change was associated with proximity to the central business district and to other aesthetically attractive neighbourhoods.…”
Section: Related Workmentioning
confidence: 99%